Stylistics and Language Variation in the L2 Classroom - Tamunobelema, Isaac (NIU Journal of Humanities; Vol 3 No 3 (2018): KIU Journal of Humanities, Vol. 3 No. 3, September 2018, 2018)
The study of language varieties globally, especially in ESL context is wide spread due to its relevance for the teaching and learning of the language and learner’s communicative ability development. Variety refers to a set of linguistic items which has similar features and distributions in human communication (speech or written) in sounds, words, grammar and so on. In the world today, there are numerous varieties of English co-existing with the idealized formal norm used in the educational setting. In the present work, we examine stylistics and other factors that are the causative agents to global language variation, and survey the value of same in ESL context which have immense benefit to speakers of the language worldwide. Keywords: Stylistics, language variation, dialect, sociolect.